QUALITY OF ANC TREATMENT AND CLIENTS SATISFACTION AT BPM Hj. ELSYE AGUSTIN - Endah Nurmahmudah; Hj. Heni Hendarsah (STIE Binaniaga, 2018)
Rapid development of global worldwide has been happening on technology, information, science and health technology including reproduction health have impacted on a very tight competition in Health Sector. Recently, the society has required quality of service, safety, comfortable and reasonable price. That is why a midwife is requested to be ready and able to respond quickly and anticipate modernization and satisfy the customers. This research aims to figure out the correlation of the quality of antenatal care (ANC) treatment and the level of clients’ satisfaction at BPM Hj. Elsye Agustin in Tasikmalaya. Data sampling technique has applied total sampling with cross sectional approach method. And data collection is primary data. Primary data is the data taken directly from the respondents which has been done by the researcher itself. Based on the result of the research, the quality of ANC treatment at BPM Hj. Elsye Agustin is good (66.3%), it explains that ANC treatment has oriented to the pregnancy needs. Pregnant women who have received pregnancy treatment at BPM Hj. Elsye Agustin are satisfied (71.4%) indicating that the expectation of pregnant women to get a satisfied treatment has been fulfilled. The correlation of the quality of ANC treatment and the clients satisfaction at BPM Hj. Elsye Agustin has identified p-value of 0.000 indicating that the clients/pregnant women are satisfied with ANC treament.Keywords: quality, antenatal care treatment, customers‟satisfaction